2022
DOI: 10.3389/fgene.2022.909095
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-mRNA Expression Profiles of Osteoclast After Conditional Knockout HIF-1α

Abstract: Background: Osteoclasts, which are multinucleated cells formed by monocyte fusion, play a key role in bone resorption. Hypoxia-inducible factor (HIF)-1α is vital for the development of osteoclasts in hypoxic environments and during bone resorption. However, additional research is required to further study the HIF-1α-dependent regulation of osteoclast differentiation at the genetic level.Methods: In our study, RNA sequencing (RNA-seq) was used to identify the expression profiles of long noncoding RNAs (lncRNAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Actually, lncRNA profiles are altered during osteoclast differentiation. The altered potential of differentiation also influences lncRNA profiles [11] . lncRNAs are involved in modulating osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, lncRNA profiles are altered during osteoclast differentiation. The altered potential of differentiation also influences lncRNA profiles [11] . lncRNAs are involved in modulating osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA participates in bone development and regeneration by regulating apoptosis, angiogenesis, and BMSCs differentiation [ 171 ]. The gene sequencing results showed that 95 lncRNAs were differentially expressed in osteoclasts knocked out of HIF-1α, suggesting that lncRNA may play a role in bone homeostasis regulation by HIF-1α [ 172 ]. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), as a highly conserved lncRNA, induces angiogenesis through the mTOR/HIF-1α pathway [ 173 ].…”
Section: The Role Of Non-coding Rna (Ncrna) In Hif-1α Regulating Bone...mentioning
confidence: 99%
“…Hypoxia-inducible factor 1α (HIF-1α) has been implicated in the pathogenesis of RA and it participates in osteoclast differentiation by regulating nutrient and energy sensors ( Fearon et al, 2016 ; Tang et al, 2019 ). Therefore, another study explored the lncRNA-mRNA expression profiles associated with HIF-1α-knockout mouse osteoclast differentiation by RNA-seq ( Tian et al, 2022 ). The results showed that lncRNA MSTRG.31769.2 and MSTRG.7566.12 were the two lncRNAs with the two highest numbers of interactions.…”
Section: Lncrnas In Joint Destruction Of Ramentioning
confidence: 99%